Association of ABO blood group with gestational diabetes mellitus in Pakistan: a case control study - Erum Saleem; Napper, Sanum; Irfan, Sheikh; Raza, Amir (Journal of the Pakistan Medical Association, 2025)
Objective: To investigate the association between blood group and development of gestational diabetes mellitus among pregnant women. Method: The retrospective, case-control study was conducted from August 2021 to May 2022 at The Aga Khan Hospital for Women, Garden Karachi, and comprised data from January to December 2020 related to women who had given live birth. All the women had been screened for gestational diabetes mellitus. Data included blood type and rhesus factor phenotype. The risk of gestational diabetes mellitus was assessed. Data was analysed using SPSS 19. Results: Of the 1,899 pregnant women, 303(16%) had gestational diabetes mellitus and 1,596(84%) were free of it. Blood type had no significant association (p=0.406) with gestational diabetes mellitus, while rhesus positivity tended to be significantly higher in the gestational diabetes mellitus group (p=0.051). Parity was the only parameter for which significant difference was found among the blood groups (p<0.05). Conclusion: There was a higher incidence of gestational diabetes mellitus in women with rhesus positivity. Key Words: Blood group, Gestational diabetes mellitus, GDM, Type 2 diabetes mellitus, Risk factors, ABO system.